Knowledge of diabetes and the practice of diabetes self-management during Ramadan fasting among patients with type 2 diabetes in Malaysia - Japar, Salimah; Ong, Swee Leong; Muhamed, Zamri; Fukunaga, Kensaku; Kobayashi, Toshihiro; Imachi, Hitomi; Sato, Seisuke; Saheki, Takanobu; Ibata, Tomohiro; Yoshimura, Takafumi; Soh, Kim Lam; Murao, Koji (Elsevier, 2022)
Background and aims: To assess the level of diabetes knowledge and its association with diabetes self-management practices during Ramadan fasting among patients with type 2 diabetes (T2D). Methods: A cross-sectional study was conducted involving a sample of Malaysian patients with T2D. Patients aged 18 years and above, and attending an outpatient diabetic unit of a government hospital were recruited between February and April 2021. A self-administered questionnaire was utilized to assess diabetes knowledge and diabetes self-management practices. Results: A total of 306 participants completed the questionnaire. Most of them were females (54.2%) and above 55 years old (75.1%). Resultantly, knowledge of diabetes was considered average among 52% of the participants. Only 9.5% of them avoided the consumption of sweet foods during iftar. Practicing late suhoor (p = 0.012) and self-monitoring of blood glucose (SMBG) (p = 0.026) during Ramadan were significantly associated with a better diabetes knowledge score. Education level (p = 0.000), working status (p = 0.030), and monthly income (p = 0.000) were significantly associated with participants’ knowledge level of diabetes. A higher proportion (72.2%) of the participants completed fasting for a month during Ramadan 2020. Meanwhile, hypoglycemia was the main reason (38.8%) for incomplete fasting. Conclusions: These findings reflect the need to improve patients’ knowledge of diabetes and diabetes self-management practices, especially during Ramadan. Such objectives could be achieved by considering the associated factors identified in this study.